Analysis of data transmission in a binary symmetric communication channel using BCH coding - T. A. Pavlenko; P. A. Lyakhov (Современная наука и инновации)
In this article, a data transfer model was compiled over a binary symmetric communication channel in MATLAB Simulink. The transmission of data encoded with BCH codes with different error probabilities was studied, as well as a comparative analysis of the percentage of corrected errors with different code redundancy was carried out.